Protective Effect of CD4+CD25+ Regulatory T Cells on Mice Model of Rheumatoid Arthritis - Rifa'i, Muhaimin (BRIN, 2011)
Naturally occurring CD4+CD25+ regulatory T (Treg) cells, a component of the innate immune response which play a key role in the maintenance of self-tolerance, have become the focus of numerous studies over the last decade. These cells have the potential to be exploited to treat autoimmune disease. These cells inhibit the immune response in an antigen-nonspecific manner by interacting with other T cells. These T cell populations actively control the properties of other immune cells by suppressing their functional activity to prevent autoimmunity but also influence the immune response to allergens as well as against tumor cells and pathogens. In this experiment we showed that induced regulatory T cells have a protective effect on mice model of rheumatoid arthritis (RA). RA mice which were injected intraperitoneally with Andrographis paniculata substrate or injected with induced regulatory T cells showed the effects of recovery. We further showed that the generation of leukocyte including B cells can be promoted by the administration of A. paniculata substrate. Tissue damage from free radicals that arise due to imperfect metabolism can be prevented by such treatment in RA model mice. Recovery effects occurred in RA model mice involves the increasing number of CD4+CD25+ regulatory T cells.